Evaluation of different bovine muscles to be applied in freeze-drying for instant meal. Study of physicochemical and senescence parameters - Messina, Valeria Marisa; Sancho, Ana Maria; Grigioni, Gabriela Maria; Fillipini, S.; Pazos, Adriana Alejandra; Paschetta, Fernanda; Chamorro, Verónica Celeste; Walsoe, Noemi Elizabeth (2018)
The aim of the present research was to evaluate bovine muscles to be subjected to freeze-drying for an instant meal. Physicochemical and senescence parameters were evaluated. The experimental part was divided into two steps. In the first step, the Semitendinosus muscle was chosen to establish methodology and experimental conditions. Physicochemical, microstructure and senescence parameters were analysed. In the second step, economic bovine muscles such as Semimembranous and Spinalis dorsi were subjected to the same methodology and conditions as in the first step in order to compare them by analysing the same parameters. L* and a* values were statistically significant (P<0.05) for Semimembranous and Spinalis dorsi muscles, showing differences among condition effects and in muscles. Humidity and water activity showed among the muscles analysed that cooked and rehydrated samples did not exhibit differences. Microstructure of Semitendinosus and Semimembranous were not separated and fragmented as occurred with Spinalis dorsi after freeze-drying. Results allowed us to select among the muscles studied that Semimembranous was suitable and economic to be used in an instant meal.